Cropping Pattern and Socio-Economic Study of Ethnic People in the Hilly Areas of Bangladesh - Barua, Joti Lal; Khan, Nazrul Islam; Barua, Sagarmay; Mohsin, Sayed Mohammad; Islam, M R (The Agriculturists, 2016)
The study was conducted at some hilly areas of Bangladesh during the period of January to May 2009 and during April to May, 2010. This was done to evaluate socio-economic condition of the ethnic people and to find out the existing cropping pattern in the hilly areas of Bangladesh. A total of 810 households from Rangamati, Khagrachari and Bandarban were selected randomly. Socio-economic profiles of the households indicated that the most household respondent belonged to thirty-forty five years age group followed by forty five- sixty years, fifteen- thirty years and sixty-seventy five years age group. This indicates that household respondents were younger (thirty-forty five years) in the study areas. It was found that, among the tribal people Marma were found highest rate of illiteracy followed by Shaontal, Tanchanga, Chakma, and Tripura. The tribal people of Tripura were not found to be below Primary level in the study area. The percentage of agriculture and service were found equal in Chakma tribal people in the study area. The Marma people were not found as a service holder because of their low education level. Cultivable land use pattern among the ethnic people revealed that out of 810 ethnic households 222 households were involved in cultivation (27.4%). It also showed that 55.4% households harvested single crop, 26.3% households harvested double crops, 10.8% households harvested triple crops in a year and only 7.5% households practiced jhum cultivation. The Agriculturists 2015; 13(1) 119-126